Studies on electrochemical mechanism of nanostructured cobalt vanadate electrode material for pseudocapacitors. (September 2021) - Arasi, S. Ezhil; Ranjithkumar, R.; Devendran, P.; Krishnakumar, M.; Arivarasan, A.
Highlights: Co3 V2 O8 nanolayers synthesized by simple co-precipitation method. Morphological analysis confirmed the layers like structure of Co3 V2 O8. Formation of Co3 V2 O8 were revealed by XPS analysis. Specific capacitance obtained was 790 F/g at 1 A/g. Cyclic stability was checked for repetitive 10000 cycles and observed 90.1 % retention. Abstract: The supercapacitive behaviour of chemically synthesized cobalt vanadate nanostructures was reported in this work. Various analytical techniques along with optical studies were utilized to investigate the crystallographic information's and optical response. Crystallographic information of the prepared nanostructures was revealed by the XRD analysis and it's formation was confirmed by the FTIR and XPS techniques. The nano-layered structural and surface morphology was observed through scanning electron microscopy and high-resolution transmission electron microscopy. Electrochemical performances in aqueous electrolytic medium were examined for supercapacitive behaviour of prepared Co3 V2 O8 . Specific capacitance value of about 790 F/g was achieved at 1 A/g current density and the superior capacitive retention of 90.1 % after 10000 cycles had been imparted by the prepared Co3 V2 O8 . Based on the results, it was confirmed that the prepared cobalt vanadate nanostructures can be used as an electrode material for future energy storage devices.